Penerapan Metode Artikulasi Sebagai Upaya Peningkatan Pemahaman Siswa:: Studi Tindakan Kelas Pada Siswa Kelas X IPA 2 MA Al Mahrusiyah Lirboyo Kota Kediri - Feri Ferdian; Zaenal Arifin (eL Bidayah: Journal of Islamic Elementary Education, 2019)
This study is a classroom action research (CAR) about the application of articulation methods in improving the understanding of class X IPA 2 students of MA Al Mahrusiyah Lirboyo Kota Kediri. This study involved 34 students consisting of 34 women. In this study, the meeting was held for 4 times, 2 meetings applied an active learning strategy for the articulation model, one meeting held a pre-test and once again held a post-test. Each meeting for each cycle is explored with planning so that each research researcher prepares: 1. Learning Implementation Plan (RPP) using articulation methods, 2. LKS, and 3. Preparing learning methods. The results of the findings of the research conducted increased learning outcomes from cycle I to cycle II, this is also because the role of the teacher performs the learning process with articulation learning models with power point learning media.